Chondrogenic activity of two herbal products; pomegranate fruit extract and avocado/soybean unsaponifiable - Ahmad Teimourinejad; Batool Hashemibeni; Hossein Salehi; Fatemeh Sadat Mostafavi; Mohammad Kazemi; Hamid Bahramian (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Articular cartilage defects aren't repaired by itself. Numerous studies have been conducted in the area of cartilage tissue engineering and some of them considered herbal products. An attempt was made in this study to compare the effects of pomegranate fruit extract (PFE), avocado/soybean unsaponifiable (ASU), and their equal proportional mixture on the chondrogenesis of human adipose-derived stem cells (hADSCs). Experimental approach: PFE was prepared through the percolation method. ASU powder was dissolved in ethanol at 10 μg/mL concentration and was sterilized. The hADSCs first were isolated, expanded in monolayer culture and identified, and next seeded on fibrin scaffolds. The hADSCs/fibrin scaffolds were divided into 4 groups of control, ASU, PFE, and PFE+ ASU and subjected to in vitro induction for 2 weeks. The control group received chondrogenic medium, other groups received chondrogenic medium plus ASU, PFE, or PFE + ASU, respectively. The MTT assay was performed for cell viability evaluation, real-time polymerase chain reaction for expression of cartilage genes, and the toluidine blue, safranin-O, and immunohistochemistry for staining of the constructs. Findings / Results: Cell viability, cartilage genes expression, matrix staining density, and collagen II protein levels in PFE samples were significantly higher than those of the other groups (P < 0.05). Histological assessments revealed more chondrogenic centers (P < 0.05) in the PFE group compared to the other groups. Conclusion and implications: In this study, it was revealed that PFE can be considered as an induction factor for future chondrogenic studies.